OC-003 Genome-wide Epigenetic Analysis In Childhood-onset Crohn's Disease Implicates Mir21. (9th June 2014) - Adams, AT; Kennedy, NA; Hansen, R; Ventham, NT; O'Leary, KR; Drummond, HE; Noble, CL; El-Omar, E; Russell, RK; Wilson, DC; Nimmo, ER; Hold, GL; et al.
Abstract : Introduction: DNA methylation influences transcriptional activity and marks sites of active transcription. Technological developments allow the rapid assessment of methylation state at 450, 000 sites across the genome. The aim of this study was to identify genes with a possible role in Crohn's disease pathogenesis, and candidate genes for methylation based diagnostic biomarkers. Methods: Using the Illumina 450k platform we analysed genome-wide DNA methylation in symptomatic children who underwent diagnostic colonoscopy, half of whom were diagnosed with CD and half had no pathology. Replication was performed in children with established CD vs. symptomatic non-disease controls. Further targeted replication by pyrosequencing was performed in adults with CD vs. healthy controls, with qPCR and microarray data to analyse expression. Results: Meta-analysis of the combined paediatric datasets (n = 66) identified 165 individual CpGs with epigenome-wide significance (Bonferroni correction) and 138 differentially methylated regions (DMR). Methylation changes were significantly enriched (p < 0.0001) in proximity to loci implicated by genome-wide association studies (GWAS). The strongest result by each approach was MicroRNA 21, within the autophagy gene VMP1 (p = 1.2 × 10 –14 ), 48 kb from GWAS SNP rs1292053. In adults with CD we replicated MIR21 hypomethylation (p = 6.6 × 10 –5, n = 172), and showed increased expression in blood (p < 0.005, n = 66). Intestinal expression increased with inflammation in CD (p = 1.4 × 10 –6, n = 99) but not controls (n = 73). Linear discriminant analysis of methylation in the paediatric discovery cohort accurately predicted disease state in the paediatric replication cohort (94% sensitivity, 100% specificity) based on methylation at two CpG sites. Conclusion: MIR21 emerges as a target for further investigation based on methylation and expression, further strengthened by other positive findings – notably dysregulation in dysplasia and colorectal cancer in IBD, an established role in T-cell differentiation, and protection from DSS-induced fatal colitis by MIR21 knockout. These data demonstrate a novel approach for identifying biological variations associated with germ-line variants identified by GWAS, and demonstrate translational potential for biomarker development and therapeutic target discovery. Disclosure of Interest: None Declared.